Mengukur dan Mengelola Risiko Cybercrime dalam E-Commerce: Peran Strategis Cybersecurity untuk Keamanan Informasi dan Perlindungan Data - Ramadian, Afzil; Fitriyani, Amanda; Sarah Novita, Neng Nanda (JURNAL ILMIAH EDUNOMIKA, 2024)
Identifying and analyzing various types of cybercrime faced by e-commerce companies, measuring the level of cybercrime risk faced by e-commerce companies, and assessing the role of cyber security are the objectives of this research. The method used is a mathematical library review. The results show that measuring risk management, especially cybercrime risk in e-commerce, can be done by assessing the level of risk available and implementing risk management strategies. Regarding the important thing regarding the role and importance of cyber security in e-commerce, namely, cyber security protects valuable e-commerce assets, such as customer data, financial information, and intellectual property, from unauthorized access, theft, or damage. The conclusion is that cybercrime risk measurement, cybersecurity, and risk management are important elements to protect e-commerce businesses from cybercrime. The limitations of this research are limited to explaining the description and elaboration of the research results of several selected journal articles. However, it does not provide further analysis regarding the relationships between the articles discussed. It is hoped that further research will sharpen understanding and solutions to the challenges of cybercrime in e-commerce.